Leave me [large type] - Forman, Gayle (Thorndike Press, A part of Gale, Cengage Learning, 2016)
"For every woman who has ever fantasized about driving past her exit on the highway instead of going home to make dinner, for every woman who has ever dreamed of boarding a train to a place where no one needs constant attention--meet Maribeth Klein, a harried working mother who's so busy taking care of her husband and twins, she doesn't even realize she's had a heart attack. Afterward, surprised to discover that her recuperation seems to be an imposition on those who rely on her, Maribeth does the unthinkable: she packs a bag and leaves. But, as is so often the case, once she gets to where she's going, she sees her life from a different perspective. Far from the demands of family and career and with the help of liberating new friendships, Maribeth is finally able to own up to secrets she has been keeping from those she loves, and from herself" --